Late Pliocene to early Pleistocene climate dynamics in western North America based on a new pollen record from paleo-Lake Idaho - Allstädt, Frederik J.; Koutsodendris, Andreas; Appel, Erwin; Rösler, Wolfgang; Reichgelt, Tammo; Kaboth-Bahr, Stefanie; Prokopenko, Alexander A.; Pross, Jörg (Palaeobiodiversity and Palaeoenvironments, 2021)
Marked by the expansion of ice sheets in the high latitudes, the intensification of Northern Hemisphere glaciation across the Plio/Pleistocene transition at ~ 2.7 Ma represents a critical interval of late Neogene climate evolution. To date, the characteristics of climate change in North America during that time and its imprint on vegetation has remained poorly constrained because of the lack of continuous, highly resolved terrestrial records. We here assess the vegetation dynamics in northwestern North America during the late Pliocene and early Pleistocene (c. 2.8-2.4 Ma) based on a pollen record from a lacustrine sequence from paleo-Lake Idaho, western Snake River Plain (USA) that has been retrieved within the framework of an International Continental Drilling Program (ICDP) coring campaign. Our data indicate a sensitive response of forest ecosystems to glacial/interglacial variability paced by orbital obliquity across the study interval, and also highlight a distinct expansion of steppic elements that likely occurs during the first strong glacial of the Pleistocene, i.e. Marine Isotope Stage 100. The pollen data document a major forest biome change at ~ 2.6 Ma that is marked by the replacement of conifer-dominated forests by open mixed forests. Quantitative pollen-based climate estimates suggest that this forest reorganisation was associated with an increase in precipitation from the late Pliocene to the early Pleistocene. We attribute this shift to an enhanced moisture transport from the subarctic Pacific Ocean to North America, confirming the hypothesis that ocean-circulation changes were instrumental in the intensification of Northern Hemisphere glaciation.